A structural model of toxic amyloid oligomers involved in type 2 diabetes - Shivani T. Shivani; Brynn E. LeMasters; Thirupathi Ravula; Harrison J. Esterly; Nikhil Maroli; Kacie L. Rich; Caitlyn R. Fields; Sidney S. Dicke; Owen A. Warmuth; Donald S. Stapleton; Mark P. Keller; Alan D. Attie; et al. (Proceedings of the National Academy of Sciences, 2026)
Amyloid oligomers of the human islet amyloid polypeptide (hIAPP) are a likely cytotoxic species driving β-cell death in type 2 diabetes, but their transient nature has precluded atomic-level structural characterization. We obtained a high-resolution structure of a physiologically relevant hIAPP oligomer. Using 2D IR spectroscopy, we identified three substitutions that slowed aggregation sufficiently for comprehensive 2D/3D NMR analysis while retaining the key wild-type structural features and cytotoxicity. The structural model reveals a dimeric assembly with N-terminal helices and a kink that facilitates an intermolecular β-sheet. The β-sheet spans the famous FGAILS portion of the sequence, helping to explain species-specific diabetes susceptibility and the origin of early-onset familial mutations. The integrated 2D IR/NMR strategy provides a unique approach to obtaining high-resolution structures of amyloid oligomers.